Konstruksi Pertanggungjawaban Pidana Pelaku Perusakan Fasilitas Umum dalam Aksi Massa - Keysa Astiara; Hartiwiningsih Hartiwiningsih; Riska Andi Fitriono (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
This research aims to analyze the criminal liability of perpetrators of arson and destruction of public facilities during demonstrations in Indonesia, as well as to examine the enforcement of criminal law against these crimes based on applicable positive law. However, in practice, demonstrations are often accompanied by anarchic actions in the form of arson and destruction of public facilities that harm the public interest and disrupt public order. The urgency of this research lies in the need to ensure that criminal liability and criminal law enforcement for acts of arson and destruction of public facilities are carried out individually and proportionally in accordance with the provisions of the old Criminal Code and the National Criminal Code, in order to prevent the general application of criminal law to participants in demonstrations. The results of the first study indicate that criminal liability for perpetrators of arson and destruction of public facilities during demonstrations has basically been regulated in the old Criminal Code and then updated in the National Criminal Code, especially regarding the crimes of arson and destruction of property. While the second enforcement of criminal law against these acts requires proportional and individual application, even though it is carried out in the context of collective mass action.